Middleware-based Support for Reconfigurable Mechatronic Systems. Issue 10 (2015) - Priego, R.; Agirre, A.; Estévez, E.; Orive, D.; Marcos, M.
Abstract: Current automation systems demand flexibility and efficiency in order to face the constant changes of the application in terms of dynamism, complexity and extensibility. To deal with these demanded requirements, automation systems have been provided with reconfiguration techniques that have allowed them to reschedule the production, to recover from a faulty situation and to update the controller at run time, among others. This paper presents a middleware architecture which provides the automation systems with the necessary mechanisms to monitor and manage several types of QoS requirements that must be assured during system operation. The design of the middleware is based on a meta-model of the automation system, composed by a set of mechatronic components containing the information related to the hardware platform, the software they implement and their internal state that allows the middleware to take decisions in order to perform the different types of reconfiguration.